Pematuhan majikan terhadap garis panduan pemberhentian pekerja: Analisis terhadap kes-kes yang diputuskan oleh Mahkamah Perusahaan - Bidin, Asiah; Abdul Wahab, Harlida; Ramli, Azlin Namili (Sekolah Pengurusan, Universiti Utara Malaysia, 2003)
The global economic recession in 1998 has so aflected Malaysia that many employers suffered financial losses or went bankrupt. During that period, retrenchment has almost become a trend in our country. In 2001, although the worst economic crisis was over, statistics showed that retrenchment still occurred in every sector. Thus, Malaysian government has introduced guidelines for retrenchment and imposed a ruling that every retrenchment done should be reported to the Labour Department. This paper analyses the retrenchment cases reported to the Industrial Court from 1998 until 2001 to determine whether the employer comply with the guideline for retrenchment. The result shows that the number of the retrenchment cases brought to the court are less than the number showed in the statistic by labour department. The Garis Panduan Pemberhentian Pekerja result also reveals that many employers do not comply with the guidelines for retrenchment.